JihÃ¢d dalam Pandangan Muhammad âAbd al-SalÃ¢m Faraj - Naharong, Abdul Muis (Program Pascasarjana UIN Sunan Ampel Surabaya, 2010)
JihÃ¢d is one of the Islamic teachings which has been extensively discussed since the last few decades due to the increasing acts of violence perpetrated by some Muslims. This article tries to join this discussion by presenting Muh ammad âAbd al-SalÃ¢m Farajâs concept of jihÃ¢d and his ideas of Islamic state and Caliphate by referring to his al-FarÃ®d ah al-GhÃ¢âibah (the Neglected Duty). We argue that Farajâs basic perception of the Egyptian politics and society at the time shaped his whole concept of state and Caliphate. We hence contend that his proposal of jihÃ¢d is born out of his disappointment of the Egyptian government and even society as far as applying Islamic law is concerned. He uncompromisingly believed that the government and society are hypocrite and apostate for distancing themselves from the divine law of God. This belief prompted four members of JihÃ¢d Organization to which Faraj belongs, to assassinate President Sadat in October 1981. By jihad, Faraj means fighting and confrontation against enemies even through bloodshed. And by enemies he means anyone who is not willing to apply Godâs law onearth. The most controversial idea that Faraj has tried to pose is that jihÃ¢d is considered to the sixth pillar of Islam, which has to be carried out by each and every member of Muslim ummah.